2011
DOI: 10.1021/nl1032588
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and Reemission of Molecules near Realistic Plasmonic Nanostructures

Abstract: The enhancement of excitation and reemission of molecules in close proximity to plasmonic nanostructures is studied with special focus on the comparison between idealized and realistically shaped nanostructures. Numerical experiments show that for certain applications choosing a realistic geometry closely resembling the actual nanostructure is imperative, an idealized simulation geometry yielding significantly different results. Finally, a link between excitation and reemission processes is formed via the theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
129
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 51 publications
3
129
0
Order By: Relevance
“…30 Such nanorods are relatively easy to fabricate in a repeatable and reliable manner and less sensitive to fabrication tolerances. 31 Furthermore, the controlled interaction between nanorods forming dipole nanoantennas 32,33 produces a very high field enhancement in the gap, making these structures well suited as ultrasensitive biosensors, 34,35 plasmonic traps 36À38 and substrates for surface-enhanced Raman spectroscopy (SERS). 39 The assembly of nanorods into more complex plasmonic oligomer structures further improves these functionalities and has been pursued by several research groups who have demonstrated Fano interference between electric and magnetic multipolar modes.…”
mentioning
confidence: 99%
“…30 Such nanorods are relatively easy to fabricate in a repeatable and reliable manner and less sensitive to fabrication tolerances. 31 Furthermore, the controlled interaction between nanorods forming dipole nanoantennas 32,33 produces a very high field enhancement in the gap, making these structures well suited as ultrasensitive biosensors, 34,35 plasmonic traps 36À38 and substrates for surface-enhanced Raman spectroscopy (SERS). 39 The assembly of nanorods into more complex plasmonic oligomer structures further improves these functionalities and has been pursued by several research groups who have demonstrated Fano interference between electric and magnetic multipolar modes.…”
mentioning
confidence: 99%
“…Using the theory of electromagnetic reciprocity [20,21], the enhancement can be interpreted to apply to spontaneous emission as well [9]. A large increase in the local density of optical states in the vicinity of the nanoantenna causes a decrease in the excited state's lifetime by the same factor as derived for the excitation enhancement.…”
Section: B Emission Enhancementmentioning
confidence: 99%
“…A quantitative expression for the enhancement in an arbitrary field is derived to then be applied to the numerically calculated field around a nanoantenna. The plasmonically enhanced field is shown to boost absorption and spontaneous emission of the quadrupole transition by 6 orders of magnitude, much more than dipole-allowed transitions, for which enhancement is in the hundreds [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not investigate the influence of deviations in geometric parameters as total length, width, curvatures etc. In another interesting work by Kern et al, the authors showed that realistic nanostructures deviating in all three dimensions from a perfectly rectangular block perform different than the ideal structures [17]. However, the authors did not relate the simulated structure quantitatively with real measured structures.…”
Section: Introductionmentioning
confidence: 99%